Annual Report on the Working of State Electricity Boards and Electricity Department October, 1995 - Planning Commission (Planning Commission, 1995)
The role of electricity sector in an economy hardly needs to be overemphasised. A review of its performance is of crucial importance, as this sector involves considerable amount of public resources and is critically relevant for economic growth. This report updates such reviews of the working of the State Electricity Boards (SEBs) and Electricity Departments (EDs) on the basis of the information provided by these agencies to the Planning Commission as a part of the discussions for the formulation of the Annual Plans.
Power and Energy Division Planning Commission
Power and Energy Division Planning Commission